Pengaruh Stres Kerja, Kecerdasan Emosional, Self-Efficacy dan Perceived Organizational Support Terhadap Komitmen Organisasi - Rini Juni Astuti; Tsabitah Qolbiyah Salimah (CV. Ulil Albab Corp, 2024)
This study aims to analyze the effect of Job Stress on Organizational Commitment, Emotional Intelligence on Organizational Commitment, Self-efficacy on Organizational Commitment, Perceived Organizational Support on Organizational Commitment. This study was conducted on teachers in four Islamic schools in Tangerang Regency, namely: Al Fityan School Tangerang, Merdeka Islamic Elementary School, Permata Hati Elementary School, Permata Hati Kindergarten School, Dauroh Integrated Islamic Junior High School, Dauroh Integrated Islamic Elementary School with a total sample of 129 respondents obtained through questionnaire data collection techniques. The sampling technique used was purposive sampling. The analysis method used is Multiple Linear Regression using the SPSS 22 program. The results of this study indicate that Job Stress has a positive effect on Organizational Commitment, Emotional Intelligence has a positive effect on Organizational Commitment, Self-efficacy has no effect and is not significant on Organizational Commitment, Perceived Organizational Support has a positive effect on Organizational Commitment.